Depression and Oxidative Stress: Results From a Meta-Analysis of Observational Studies - Palta, Priya (Psychosom Med, 2013)
OBJECTIVE: To perform a systematic review and meta-analysis that quantitatively tests and summarizes the hypothesis that depression results in elevated oxidative stress and lower antioxidant levels. METHODS: We performed a meta-analysis of studies that reported an association between depression and oxidative stress and/or antioxidant status markers. PubMed and EMBASE databases were searched for articles published from January 1980 through December 2012. A random-effects model, weighted by inverse variance, was performed to pool standard deviation (Cohen’s d) effect size estimates across studies for oxidative stress and antioxidant status measures, separately. RESULTS: Twenty-three studies with 4980 participants were included in the meta-analysis. Depression was most commonly measured using the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria. A Cohen’s d effect size of 0.55 (95% confidence interval = 0.47–0.63) was found for the association between depression and oxidative stress, indicating a roughly 0.55 of 1-standard-deviation increase in oxidative stress among individuals with depression compared with those without depression. The results of the studies displayed significant heterogeneity (I(2) = 80.0%, p < .001). A statistically significant effect was also observed for the association between depression and antioxidant status markers (Cohen’s d = −0.24, 95% confidence interval = −0.33 to −0.15). CONCLUSIONS: This meta-analysis observed an association between depression and oxidative stress and antioxidant status across many different studies. Differences in measures of depression and markers of oxidative stress and antioxidant status markers could account for the observed heterogeneity. These findings suggest that well-established associations between depression and poor heath outcomes may be mediated by high oxidative stress.